2021
DOI: 10.1111/pan.14311
|View full text |Cite
|
Sign up to set email alerts
|

The ulnar artery: A site suitable for arterial cannulation in pediatric patients

Abstract: Background: Historically, the ulnar artery has rarely been considered for arterial cannulation as it is less easily palpated than the radial artery. With the current routine use of ultrasound in pediatric patients, the ulnar is as accessible as the radial and could be viewed as an equivalent site for cannulation. Aims:The purpose of this study was to compare ulnar and radial artery suitability for arterial cannulation in pediatric patients using 2-dimensional ultrasound. Methods:We examined the ulnar and radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…Comparing the UA and RA in children, the previous reports of Latham et al indicated a larger RA diameter, 5 while Roux et al reported a larger UA diameter 6 . However, in this study, there were no statistically significant differences between the diameters of the UA and RA in all age groups (Figure 3).…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Comparing the UA and RA in children, the previous reports of Latham et al indicated a larger RA diameter, 5 while Roux et al reported a larger UA diameter 6 . However, in this study, there were no statistically significant differences between the diameters of the UA and RA in all age groups (Figure 3).…”
Section: Discussioncontrasting
confidence: 64%
“…[1][2][3][4] However, there are few clinical studies on the UA approach in children and comparing the diameter of UA and RA. [5][6][7][8] It has also been reported that a depth of 2-4 mm from the skin surface increases the success rate of arterial cannulation. 9 Recently, a new transcutaneous vascular visualization device, the Mill Suss™ Vascular Visualization Device (Nippon Covidien Ltd.), has been introduced.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This patient population often requires specialized pain management strategies secondary to increased muscle tone and spasticity, which can be worsened by inadequate pain control. 1 While there have been many surgery-specific guidelines published in the adult population, there is far less available literature for the pediatric population. [2][3][4][5][6] Prior to development of our ERAS protocol, we noticed that patients that were not eligible to have an epidural placed (eg, posterior spinal fusion, baclofen pump) and who had single-shot peripheral nerve blocks placed appeared to have similar pain management outcomes and were leaving the hospital earlier compared to our patients who had an epidural placed.…”
Section: Enhanced Recovery After Surgery In Pediatric Cerebral Palsy ...mentioning
confidence: 99%
“…
We read with great interest the article by Roux et al 1 comparing the size and depth of radial and ulnar arteries in pediatric patients from birth to 6 years of age. The authors reported that the ulnar artery was larger than the radial artery in 60% of the patients, which might be advantageous for ultrasound-guided peripheral arterial cannulation.
…”
mentioning
confidence: 99%